Frequency and Risk Factors of Re-hospitalization in Geriatric Inpatient Wards: A Multicenter Retrospective Analysis. Issue 1 (1st January 2023) - Kayhan Kocak, Fatma Ozge; Sahin, Sevnaz; Taşkıran, Emin; Simsek, Hatice; Daylan, Ayse; Arman, Pinar; Dikmeer, Ayse; Kılıc, Furkan; Balci, Cafer; Tosun Tasar, Pınar; Doventas, Alper; Yavuz, Burcu Balam; et al.
ABSTRACT: Purpose: We aimed to evaluate frequency and risk factors of re-hospitalization which are not stated in comorbidity indexes in geriatric wards. Methods: A total of 585 patients who were admitted to tertiary care geriatric inpatient clinics at least once between 1 September 2017 and 1 September 2018 and who survived to discharge during initial hospitalization were included in this cross-sectional retrospective multicenter study. Results: Overall, 507(86.7%) patients were hospitalized once for treatment during the study period, while re-hospitalization occurred in 78(13.3%) patients. Rates of previous surgery (10.3 vs. 3.0%, p = .006), urinary incontinence (UI) (50.0 vs. 36.3%, p = .021), controlled hypertension (64.1 vs. 46.4%, p = .024), malnutrition (55.1 vs. 29.6%, p = .014) were significantly higher in re-hospitalized patients. Re-hospitalized patients were younger (mean ± SD 76.4 ± 8.3 vs. 79.6 ± 7.9 years, p = .002) than once-hospitalized patients. Multivariate logistic regression analysis revealed the younger patient age (OR, 0.942, 95% CI 0.910 to 0.976, p = .001), higher Modified Charlson Comorbidity Index (MCCI) score (OR, 1.368, 95% CI 1.170 to 1.600, p < .001) to significantly predict the increased risk of re-hospitalization. Conclusions: Our findings showed that previous history of surgery and geriatric syndromes such as UI, malnutrition were determined to significantly predict the increased risk of re-hospitalization. We suggest that these risk factors be added to prognostic tools designed for elderly patients.